Applying a Reference Objects Preselection Algorithm to Real-World Data - Bondarenko, N. N. (Pattern recognition and image analysis, 2018)
The problem of optimal selection of learning objects is investigated. The effectiveness of the previously proposed iterative method for generating sets of relevant precedents is demonstrated on real-world data.